Lack of aconitase in glyoxysomes and peroxisomes. - Courtois-Verniquet, F (1993)
The aim of this work was to find out whether aconitase [citrate (isocitrate) hydro-lyase, EC 4.2.1.3] which is rapidly inactivated by H2O2, is present in the microbodies from plant cells. The separation of intact organelles from castor-bean (Ricinus communis) endosperm and potato (Solanum tuberosum) tuber indicated that aconitase activity is essentially limited to the mitochondria and cytosol fraction, but was not detected in highly purified castor-bean endosperm and potato tuber peroxisomes. An isotropic e.p.r. signal of the type expected for the 3Fe cluster of oxidized aconitase was not detected in microbodies. In immunoblot analyses, antibodies raised against potato tuber mitochondrial aconitase did not cross-react with any glyoxysomal or peroxisomal protein. Positive reactions were found for cytosol fraction and mitochondria of castor-bean endosperm. The operation of the full glyoxylate cycle in isolated glyoxysomes requires the presence of aconitase in the incubation medium. It is concluded that glyoxysomes are probably devoid of aconitase and that the glyoxylate cycle requires a detour via the cytosol, which contains a powerful aconitase activity.